تغيرات الزيادة العربية والإندونيسية و تأديّتها في تعليم اللغة العربية - Muhamad Isbah Habibii (Abjadia, 2017)
منذ 28 أكتوبر 1928 تكون اللغة الإندونيسية لغة رسمية في الإندونيسيا، وهي من اللغات الأوسترونية. ويبدو واضحا من الاختلافات الأنفة الذكر أنها يسبب لأخطأ دارس اللغة العربية. الدارس كثيراما يبدأ الأخطأ في عملية تدريس اللغة العربية. ومن بين اسباب الأخطأ هي خصائص اللغة الثانية أو لغة الهدف لا توجد في لغته الأم. أما المنهج الذي انتجته الباحثة في هذه الدراسة فهو البحث الوصفي والمنهج البحث المكتبي والميداني، ولتحقيقه استخدم هذا البحث البحث الإجرائي. ونتائج هذا البحث قسمان. الأول: وجوه التشبّهات و الإختلافات: فوجوه التشبّهات توجد 10 تشبّهات. ووجوه الإختلافات توجد 25 إختلافات. والثاني: تأديّته في تعليم اللغة العربية. أ) إن وجوه الإختلافات تؤدي إلى مواجهة الصعوبة في مهارة الكتابة. فينبغي للمدرس أن يختار وجوه التشبّهات؛ ب) هذه التقايلية كالأساس في صياغ التقنيق التعليمي في تعليم اللغة العربية ل سيما في ترتيب المواد اللغة لتكون سهلة ولائقة حسب المستوىSince October 28, 1928, Indonesian language is officially used by the Indonesian as national language. And when viewed from the clump of this language includes Austronesian based on the classification, and Arabic language includes semid based on the classification. This difference of classification leads to errors in learners’  language. Such as the first language fragmentation of a second language (Arabic) which is also called Interference language. To analyze this research,  the researcher used contrastive analysis. The instruments used in this study are documentation, observation and interviews. The results of this study are divided into two poin, including: similarities and differences Affix Arabic And Indonesian. The first: aspect of the similarities there are ten similarities, and aspects of the two aspects of difference there are twenty-five differences. Second: The implication in maharah kitabah are: a) The contrastive analysis can be used to predict the mistakes of students studying foreign languages. The points of difference in each of the first and second language levels will give students difficulties in learning the second language. Preferably the same items will make it easier for students to learn a second language; b) The contrastive analysis can provide a comprehensive and consistent contribution and as a means of controlling the preparation of teaching materials and second language lessons efficiently. By comparison of differences in each level of language analysis, the material can be arranged according to the level of difficulty of each level.